2006
DOI: 10.1161/01.atv.0000197795.56960.64
|View full text |Cite
|
Sign up to set email alerts
|

Lesional Overexpression of Matrix Metalloproteinase-9 Promotes Intraplaque Hemorrhage in Advanced Lesions But Not at Earlier Stages of Atherogenesis

Abstract: Background-Matrix metalloproteinase-9 (MMP-9) is involved in atherosclerosis and elevated MMP-9 activity has been found in unstable plaques, suggesting a crucial role in plaque rupture. This study aims to assess the effect of MMP-9 on plaque stability in apolipoprotein E-deficient mice at different stages of plaque progression. Methods and Results-Atherosclerotic lesions were elicited in carotid arteries by perivascular collar placement. MMP-9 overexpression in intermediate or advanced plaques was effected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
1
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(133 citation statements)
references
References 44 publications
5
122
1
5
Order By: Relevance
“…Similarly, increased expression of MMP-3, MMP-12, and MMP-13 has been reported not only in atherosclerotic lesions but also in aneurysms in LDLR 2/2 (26). In ApoE 2/2 , overexpression of MMP-9 in macrophages has been observed in advanced atherosclerotic lesions and is commonly associated with plaque rupture (27) and intraplaque hemorrhage (28). Conversely, in ApoE 2/2 , MMP-9 deficiency is reported to be associated with reduced atherosclerosis, medial layer attenuation (29), and vascular remodeling (30).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased expression of MMP-3, MMP-12, and MMP-13 has been reported not only in atherosclerotic lesions but also in aneurysms in LDLR 2/2 (26). In ApoE 2/2 , overexpression of MMP-9 in macrophages has been observed in advanced atherosclerotic lesions and is commonly associated with plaque rupture (27) and intraplaque hemorrhage (28). Conversely, in ApoE 2/2 , MMP-9 deficiency is reported to be associated with reduced atherosclerosis, medial layer attenuation (29), and vascular remodeling (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, over-expressing a mutated form of MMP-9 that becomes fully auto-activated produced high levels of plaque instability (19). Adenovirus-mediated over-expression of MMP-9 produced instability of advanced plaques caused by collar implantation into ApoE null mice (20). These studies illustrate an important principle: both the nature of MMPs expressed and the level of activity are crucial in determining whether controlled remodelling or matrix destruction and hence instability occurs.…”
Section: Intravascular Biology Meeting 2008mentioning
confidence: 96%
“…114 Thus, the results appear to differ depending on whether endogenous MMP-9 is deleted, 112 or exogenous MMP-9 is overexpressed in the lesions. 113,114 Overexpressing either TIMP-1 or TIMP-2 by systemic injection of adenovirus, Johnson and colleagues showed that TIMP-2 but not TIMP-1 inhibited plaque rupture. 106 A limitation of most of these studies is that rupture was reported at only one location in the arterial system, and it is not certain whether similar rupture events occur elsewhere.…”
Section: Mmps and Plaque Rupturementioning
confidence: 99%